Normative Values for Active Lumbar Range of Motion in Children and Confounding Factors that Affects the Active Lumbar Range of Motion - Sanjeevni Sawale; Richa Bisen; Senthil Kumar E (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2015)
Purpose: The purpose of this study was to establish normative values for active lumbar movement in children five, seven, nine, and 11 years of age and to find the confounding factors that affect the lumbar range.  Methods: End range active flexion, extension, and right- and left-side bending of the lumbar spine were measured for 400 normally developing children (200 girls, 200 boys) using dual inclinometric technique. Means were determined for each motion by age and sex. Group relationships were explored.  Results: Normative values for lumbar spine cardinal plane movements were identified. Reduced lumbar movement was found in the 11-year-old group compared with the 5-year-old group in both girls and boys. Flexibility levels were defined using percentiles as poor (<25th), moderate (between 25th and 75th), good (between 75th and 95th), and very good (>95th) respectively. The mean value for forward flexion, extension right and left lateral flexion for all participants was 55.9+17, 21.8+6, 15.2+5.1 and 14.9+5.  Conclusion: Normative data for cardinal plane movements of the lumbar spine provide therapists with a baseline for assessing spinal mobility of children of these ages.